Estimation of influence of uniflow closed-bottom thimbles on subshrinking liquidation - E. V. Ivanov; A. V. Olenchenko; M. E. Kontanistov; A. I. Nosovets (Литьë и металлургия)
There is developed the technology of steel cast at MNLZ- 3 with protection of metal stream against secondary oxidation in zone flushing bowl-crystallizer through closed-bottom quartz immersible thimbles. At cast of cord steel grades at MNLZ- 3 the application of closed-bottom quartz immersible thimbles of type SKSB-79 enabled to decrease the density of metal- oxide impurities with diameter 5,5 mm by 29 %, and Significance subshrinking liquidation by 14,2 and 25 %.